DEVELOPMENT OF AUGMENTED REALITY LEARNING MEDIA TO IMPROVE MATHEMATIC SPATIAL ABILITY - Gunawan Gunawan; Nuhyal Ulia; Agung Muhammad Iqbal; Jaka Wijaya Kusuma (International Journal of Economy, Education and Entrepreneurship, 2022)
This study aims to develop Augmented Reality (AR) learning media to improve the mathematical spatial ability of junior high school students on geometry material. The method used is research and development (R&D). The learning media developed in this research is Augmented Reality, called Virtual Geometry. The research instrument consisted of a validation sheet, an observation sheet, and a spatial ability test. Data collection techniques used are unstructured interviews and observations. Data analysis techniques in this study include validity, practicality, and effectiveness. The results showed that Augmented Reality-based Virtual Geometry learning media met the valid and practical aspects. The media is effective in increasing spatial ability